Hantu Populer di Film Indonesia - Zein Muffarih Muktaf (Program Studi Ilmu Komunikasi, 2008)
Ghost myth is popular in Indonesia. Myth specter appears from the primitive to the modern era. Ghost phenomenon increasingly popular after the movies began to spook a lot of pop. There are several factors that emerged a large number of ghost movies in Indonesia today. One of them is the Eastern faith that believes